Integrating Qur’anic Moral Values through the Bina Pribadi Islami (BPI) Program: A Case Study in an Islamic School in Indonesia - Salsabila, Amalia; Salim, Hakimuddin (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
This study examines how Qur’anic moral values are integrated into a school-based character development program through the Bina Pribadi Islami (BPI) framework at SMPIT Nur Hidayah Surakarta, an Islamic integrated school in Indonesia. The study addresses the gap between normative formulations of moral education and their practical implementation in school settings. A qualitative case study design was employed, with data collected through semi-structured interviews, field observations, and document analysis. The primary informants consisted of a BPI mentor and an Islamic Education teacher, while additional data were obtained from observations of student activities and institutional documents to support triangulation. The analysis focused on selected Qur’anic teachings, particularly those reflected in Surah Al-Kautsar and Surah Al-Ma’un, as a basis for understanding the integration of moral values. The findings indicate that the integration of moral values is carried out through interconnected practices, including structured habituation, mentoring-based interaction, and the operationalization of values in both worship and social activities. These practices are supported by institutional mechanisms such as the 10 muwashofat framework, continuous monitoring through mutaba’ah amal yaumiyah, and the involvement of teachers across subject areas. The integration process reflects a systematic sequence of value identification, behavioral translation, habituation, evaluation, and follow-up guidance, allowing Qur’anic values to be embedded in students’ daily experiences. The findings indicate that the BPI program represents a structured and contextually grounded approach to integrating Qur’anic moral values within school-based character education, in which religious values are translated into sustained practices supported by institutional systems and daily interaction.